Structure variation of a sidewall quantum well on a GaN nanorod. (16th December 2016) - Zhang, Xu; Tu, Charng-Gan; Kiang, Yean-Woei; Yang, C C
Abstract: A theoretical model for evaluating the height-dependent variations of quantum well (QW) thickness and In concentration in a sidewall QW of a single- or two-section GaN nanorod (NR) is proposed. By reasonably choosing modeling parameter values, the obtained numerical results are quite consistent with the available experimental data. In particular, the model clearly demonstrates the increasing trends of QW thickness and In concentration with height on a sidewall of a single-section NR. Also, it successfully explains the larger QW thickness and higher In concentration in the upper uniform section, when compared with the lower uniform section, in a two-section NR. In this model, three III-group adatom supply sources are considered for sidewall deposition on a single-section NR, including the downward diffusion of adatoms collected on the slant facets at the NR top, the upward diffusion of adatoms collected on the NR base, and the direct adsorption of atoms on the sidewall from the vapor phase. For a two-section NR, the upward and downward diffusions of adatoms collected on the slant facets of the tapering section between the two uniform sections serve as extra adatom supply sources.